2016
DOI: 10.1091/mbc.e15-11-0756
|View full text |Cite
|
Sign up to set email alerts
|

Src-dependent phosphorylation of caveolin-1 Tyr-14 promotes swelling and release of caveolae

Abstract: Src-induced phosphorylation of Cav-1 is analyzed using live TIRF and FRET microscopy, as well as by biochemical analysis. Cav1 phosphorylation destabilizes plasma membrane–associated Cav-1 oligomers and thereby is crucial for regulating the fission of caveolae from the plasma membrane in vascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 69 publications
8
101
0
Order By: Relevance
“…These data indicate that Tyr-940 is a key residue involved in the intramolecular interaction, and consistently it was reported that Tyr-940 of DENND3 is phosphorylated in rat brain (22). Because of the aromatic ring of tyrosine, there is no natural amino acid substitute that creates an ideal phosphomimetic mutant, but many examples do exist in which mutation of Tyr to Asp or Glu has been used successfully to mimic phosphorylated tyrosine (23)(24)(25)(26)(27). Theoretically, if the effect of the phosphorylation is due primarily to the negative charge of the phospho group, Asp or Glu should mimic phosphorylated tyrosine.…”
Section: Identification Of Tyr-940 As a Key Residue Involved In The Isupporting
confidence: 67%
“…These data indicate that Tyr-940 is a key residue involved in the intramolecular interaction, and consistently it was reported that Tyr-940 of DENND3 is phosphorylated in rat brain (22). Because of the aromatic ring of tyrosine, there is no natural amino acid substitute that creates an ideal phosphomimetic mutant, but many examples do exist in which mutation of Tyr to Asp or Glu has been used successfully to mimic phosphorylated tyrosine (23)(24)(25)(26)(27). Theoretically, if the effect of the phosphorylation is due primarily to the negative charge of the phospho group, Asp or Glu should mimic phosphorylated tyrosine.…”
Section: Identification Of Tyr-940 As a Key Residue Involved In The Isupporting
confidence: 67%
“…In general, Src-mediated Cav1 phosphorylation on Tyr14 has been demonstrated to be essential for Cav1 signaling and Cav1 endocytosis because phosphorylation of Cav1 leads to separation of neighboring negatively-charged N-terminal phospho-tyrosine residues, promoting swelling of caveolae followed by their release from the plasma membrane4748. Hereby Src has also been shown to play an important role in PCa development and progression because Src can signal through focal adhesion kinase (FAK) in response to integrin activation, which has been implicated in many aspects of tumor biology, such as cell proliferation, metastasis and angiogenesis4950.…”
Section: Discussionmentioning
confidence: 99%
“…eNOS is activated by phosphorylation at multiple sites, and lowered p-eNOS levels indicate a decreased ability to vasodilate and an increased propensity for vessel wall hyperplasia [35,36]. Cav-1 is a scaffolding protein essential in the cellular transport of macromolecules, and its phosphorylation leads to the destabilization of this process [37]. A decrease in the phosphorylation of Cav-1 thus indicates a decreased ability of EC to mediate growth, contributing to vessel wall thickening.…”
Section: Discussionmentioning
confidence: 99%